Effect of AC electric field with the changeable in time frequency on trapped particles - Antufuev, A.Yu.; Shishkin, A.A. (Вопросы атомной науки и техники, 2002)
The effect of alternating electric field on the particle detrapping in two kinds of magnetic configurations with different || modulation is considered here.